COVID-19 Outbreaks Linked to Workplaces, 23 US Jurisdictions, August–October 2021. (March 2023) - Luckhaupt, Sara E.; Horter, Libby; Groenewold, Matthew R.; de Perio, Marie A.; Robbins, Cheryl L.; Sweeney, Marie Haring; Thomas, Isabel; Valencia, Diana; Ingram, Amanda; Heinzerling, Amy; Nguyen, Alyssa; Townsend, Emily B.; et al.
Objectives: Early in the COVID-19 pandemic, several outbreaks were linked with facilities employing essential workers, such as long-term care facilities and meat and poultry processing facilities. However, timely national data on which workplace settings were experiencing COVID-19 outbreaks were unavailable through routine surveillance systems. We estimated the number of US workplace outbreaks of COVID-19 and identified the types of workplace settings in which they occurred during August–October 2021. Methods: The Centers for Disease Control and Prevention collected data from health departments on workplace COVID-19 outbreaks from August through October 2021: the number of workplace outbreaks, by workplace setting, and the total number of cases among workers linked to these outbreaks. Health departments also reported the number of workplaces they assisted for outbreak response, COVID-19 testing, vaccine distribution, or consultation on mitigation strategies. Results: Twenty-three health departments reported a total of 12 660 workplace COVID-19 outbreaks. Among the 12 470 workplace types that were documented, 35.9% (n = 4474) of outbreaks occurred in health care settings, 33.4% (n = 4170) in educational settings, and 30.7% (n = 3826) in other work settings, including non–food manufacturing, correctional facilities, social services, retail trade, and food and beverage stores. Eleven health departments that reported 3859 workplace outbreaks provided information about workplace assistance: 3090 (80.1%) instances of assistance involved consultation on COVID-19 mitigation strategies, 1912 (49.5%) involved outbreak response, 436 (11.3%) involved COVID-19 testing, and 185 (4.8%) involved COVID-19 vaccine distribution. Conclusions: These findings underscore the continued impact of COVID-19 among workers, the potential for work-related transmission, and the need to apply layered prevention strategies recommended by public health officials.